The book of Genesis and the Genesis Apocryphon : a literary and thematic comparison - Weener-Hartney, Johanna (Kaplan Centre for Jewish Studies, 2014)
The main focus in this thesis is the understanding of Genesis 12: 1- 13: 4 and its development in the Genesis Apocryphon, one of the re-written Bible text, dealt with in this dissertation. Reading the Genesis Apocryphon, it draws your attention to firstly find out why, and secondly, to see how the author/s of this scroll re-wrote the above-mentioned passage in Genesis. The focus of the Genesis account is particularly on Abram leaving the Promised Land of Egypt, and consequently, what may be regarded as his ill behaviour towards Sarai, his wife, while they were in Egypt. Abraham's leave-taking of the Promised Land, and his behaviour towards his wife are unexpected, for Abram had followed God's calling, and had been promised Canaan for his and Sarai's offspring, However interfers, and lead Abram back on his steps.